Wonder and Heartthrob. The Aesthetic Dimension of the Sacred - Marco Dallari (University of Bologna, 2020)
Sacred means separate. Often the terms sacred and religious are used as synonyms, but instead, the distinction must be underlined because the sacred precedes history and religions are instead produced and contained by it. The sphere of the sacred, imbued with mystery and capable of arousing, with its epiphanies, wonder and fear, is explored with the languages of philosophy, of science, in particular of psychology and psychoanalysis, and of religion which, with its precepts and commandments, often makes the reserve of silence and the vertigo of the openness typical of sacredness unintelligible. Probably the most suitable languages to represent the sacred are those able to inhabit the aesthetic dimension. Music, plastic and visual arts, poetic writings, thanks to the margin of further significance and meaning that characterizes them, and to the hermeneutical procedures that impose on those approaching them, can protect the margin of mystery that characterizes the sacred.